2010
DOI: 10.1519/jsc.0b013e31819b79cf
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Acute Bout of Whole Body Vibration Exercise on Muscle Force Output and Motor Neuron Excitability

Abstract: McBride, JM, Nuzzo, JL, Dayne, AM, Israetel, MA, Nieman, DC, and Triplett, NT. Effect of an acute bout of whole body vibration exercise on muscle force output and motor neuron excitability. J Strength Cond Res 24(1): 184-189, 2010-The purpose of the current investigation was to assess the effect of an acute bout of whole body vibration (WBV) exercise on muscle force output and motor neuron excitability. Nineteen recreationally trained college-aged males were randomly assigned to a WBV (n = 10) or a sham (S, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 23 publications
(41 reference statements)
7
54
2
1
Order By: Relevance
“…A small decrease in isometric torque was observed at knee angle of 60° in the WBV group and suggests that a certain fatigue was caused by vibration. This is further supported by other publications with comparable vibration settings (3-to-10 times 60-second periods of isometric squatting at 70-to-50° of knee flexion; vibration frequency: 30 Hz; vibration amplitude: 4-8 mm), reporting decreases in muscular strength after a single session of WBV (de Ruiter et al 2003;Erskine et al 2007;Jordan et al 2010) Conversely, some authors have reported strength increases immediately after WBV (Bosco et al 1999;Bosco et al 2000;Mc Bride et al 2010). However, this phenomenon only seems ephemeral, as suggested by its disappearance after a few minutes (Stewart et al 2009;Torvinen et al 2002).…”
Section: Torque-angle Relationshipsupporting
confidence: 69%
See 1 more Smart Citation
“…A small decrease in isometric torque was observed at knee angle of 60° in the WBV group and suggests that a certain fatigue was caused by vibration. This is further supported by other publications with comparable vibration settings (3-to-10 times 60-second periods of isometric squatting at 70-to-50° of knee flexion; vibration frequency: 30 Hz; vibration amplitude: 4-8 mm), reporting decreases in muscular strength after a single session of WBV (de Ruiter et al 2003;Erskine et al 2007;Jordan et al 2010) Conversely, some authors have reported strength increases immediately after WBV (Bosco et al 1999;Bosco et al 2000;Mc Bride et al 2010). However, this phenomenon only seems ephemeral, as suggested by its disappearance after a few minutes (Stewart et al 2009;Torvinen et al 2002).…”
Section: Torque-angle Relationshipsupporting
confidence: 69%
“…However, discrepant findings have since been reported and the immediate effects of WBV on neuromuscular performance are still debated. For instance, authors observed gains in jump performance (Bosco et al 2000;Colson and Petit 2013) and lower body strength (Mc Bride et al 2010;Stewart et al 2009;Torvinen et al 2002) but others failed to see any improvement in muscular function (Kelly et al 2010;Yeung et al 2014) or even found reductions in maximum torque following a single WBV intervention (de Ruiter et al 2003;Erskine et al 2007;Jordan et al 2010). These inconsistent findings are often explained by differences in vibration parameters or by the time elapsed between the WBV session and the measurements (Stewart et al 2009;Torvinen et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There are some research studies that conclude that using WBV prior to vertical jump performance induces a post-activation potentiation (PAP) response [5,35]. PAP has been shown to increase voluntary force development during muscle actions [40] but can induce fatigue if the intensity is too high or there is not sufficient rest periods before performance [41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to increase performance variables, optimal rest intervals are critical when utilizing whole-body vibration. Previous research have shown conflicting results using varying rest intervals following acute bouts of WBV, from immediately post to 10 min [5,8,10,12,22,23,35,36]. To our knowledge there is no current literature that has investigated this vibration protocol with these specific rest times comparing athletes versus non-athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Acute changes in motor output due to WBV are most often associated with neural factors such as increases in sensitivity of the primary muscle spindle afferent fibers, resulting in facilitation of homonymous alpha motor neurons. 22 These mechanisms, in turn, may lead to increased motor unit recruitment, increased firing frequency, and/or improved synchronization, 23,24 and ultimately result in non-voluntary muscular contraction, i.e. tonic vibration reflex.…”
Section: Muscle Activity During Wbvmentioning
confidence: 99%